Analysis and assessment of a critical event during an underground coal gasification experiment. (January 2015) - Krause, Eugeniusz; Krzemień, Alicja; Smoliński, Adam
Abstract: The main goal of the study presented in this paper was to analyse the mechanisms affecting an Underground Coal Gasification (UCG) process and to identify possible deviations of the system from normal work to limit, or even avoid, losses. The UCG process is one of the most innovative technologies connected with the exploitation of coal deposits that are currently being tested and developed all around the world. It allows the conversion of a coal seam into gas under in situ conditions of high temperature with the use of gasifying agents such as air, oxygen, steam or with a mixture of them. The paper presents the results of the analysis and assessment of a critical event during the process: a dangerous gas accumulation that occurred during an underground coal gasification experiment in the Experimental Mine "Barbara" of the Central Mining Institute (Poland). The UCG experiment using the shaft method is described, together with its monitoring system and the problems that appeared during the process. The application of the Fault Tree Methodology allowed the establishment of the main factors that may lead to the explosion and to present possible scenarios of its occurrence. Moreover, calculations were carried out to evaluate the risk level of explosion for the gas mixture and the minimum level of oxygen in the mixture that is necessary to initiate an explosion. These calculations were based on a modification of the formula proposed by Le Chatelier. During the course of the underground experiment, original information of the process behaviour has been acquired that can be used in the preparation of other UCG experiments in operational mines to guarantee the safety and the stability of the process. Highlights: Possible problems during the Underground Coal Gasification process were identified. A gas leakage from the reactor during the UCG experiment was described. The Fault Tree Methodology was implemented for risk assessment. Calculations of risk level of explosion were carried out. A formula proposed by Le Chatelier was modified.